2001
DOI: 10.1038/nm1001-1133
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pancreatic β-cell growth and survival by the serine/threonine protein kinase Akt1/PKBα

Abstract: The physiological performance of an organ depends on an interplay between changes in cellular function and organ size, determined by cell growth, proliferation and death. Nowhere is this more evident than in the endocrine pancreas, where disturbances in function or mass result in severe disease. Recently, the insulin signal-transduction pathway has been implicated in both the regulation of hormone secretion from beta cells in mammals as well as the determination of cell and organ size in Drosophila melanogaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
436
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(470 citation statements)
references
References 30 publications
24
436
0
10
Order By: Relevance
“…Transgenic mice that overexpress Igf2 specifically in beta cells had beta cell hyperplasia by day 3 of life [24,25]. Similar results of beta cell hyperplasia were obtained in transgenic mice overexpressing Igf1 or thymoma viral proto-oncogene 1 (Akt1) specifically in beta cells [25][26][27]. Beta-cell-specific knockout of Irs2 led to adult beta cell mass reduction [28].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Transgenic mice that overexpress Igf2 specifically in beta cells had beta cell hyperplasia by day 3 of life [24,25]. Similar results of beta cell hyperplasia were obtained in transgenic mice overexpressing Igf1 or thymoma viral proto-oncogene 1 (Akt1) specifically in beta cells [25][26][27]. Beta-cell-specific knockout of Irs2 led to adult beta cell mass reduction [28].…”
Section: Discussionsupporting
confidence: 55%
“…Exogenous IGF1 and IGF2 are able to suppress apoptosis in isolated islets from pre-diabetic non-obese diabetic mouse following exposure to proinflammatory cytokines [41]. Igf1 overexpression in transgenic mice protects islets from further apoptotic cell death in response to streptozotocin [25,27]. Similar results of protection against apoptosis were found in transgenic mice with overexpression of effectors of the IGF signalling pathway [27,42].…”
Section: Discussionsupporting
confidence: 53%
“…Consistently with this result, PKB has been shown to play an important role in the regulation of beta cell mass. Indeed, two recent studies have demonstrated that transgenic mice expressing a constitutively active form of PKB had significantly greater beta cell mass than control animals [59,60]. Moreover, these transgenic mice were protected from streptozotocininduced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, three closely related isoforms of PKB are encoded by distinct genetic loci: PKBα/Akt1, PKBβ/Akt2 and PKBγ/Akt3 [23]. The pancreatic beta cell contains high levels of PKBα [24], and the targeted overexpression of PKBα in vivo enhances beta cell mass and function through effects on cell number and cell size [25,26]. Indeed, PKB is increasingly implicated as a key player in the regulation of beta cell growth and survival [27].…”
Section: Introductionmentioning
confidence: 99%